Heart disease in pregnancy and adverse outcomes: an umbrella review - Zhang, Jiani; Ren, Yuxin; Li, Bingjie; Cao, Qi; Wang, Xiaodong; Yu, Haiyan (Frontiers in Medicine, 2025)
BackgroundHeart disease in pregnancy encompasses both congenital heart disease and maternal-acquired heart disease, both of which are associated with an increased risk of various adverse outcomes for mothers and their offspring.ObjectiveThe objective of the study was to review and summarize the evidence regarding the association between heart disease in pregnancy and adverse outcomes in mothers and their offspring.Data sourcesA comprehensive search was conducted in Embase, PubMed, Web of Science, and the Cochrane Database of Systematic Reviews from inception to March 2024. The protocol for this review was registered in PROSPERO (CRD42024519144).Study eligibility criteriaThis review included systematic reviews and meta-analyses that examined the association between heart disease in pregnancy and adverse outcomes for mothers and their offspring.Study appraisal and synthesis methodsData were independently extracted by two reviewers. The quality of the systematic reviews and meta-analyses was assessed using the A Measurement Tool to Assess Systematic Reviews 2 (AMSTAR2), while Grading of Recommendations, Assessment, Development, and Evaluation (GRADE) was used to evaluate the strength of the evidence for each outcome.ResultsA total of 12 meta-analyses and systematic reviews were included, which documented 156 adverse outcomes for mothers and 65 adverse outcomes for offspring. Evidence was found for both primary and secondary adverse outcomes. Adverse outcomes for mothers were death, cardiac events (cardiac arrest, heart failure, surgery, arrhythmia, anesthesia or sedation, endocarditis, mitral regurgitation, myocardial infarction, NYHA III–IV, restenosis, syncope, and others), pulmonary events (respiratory failure, pulmonary edema, and respiratory support), embolism, cerebrovascular events, postpartum hemorrhage, arterial events, delivery mode, and hospital stay. Adverse outcomes for offspring were death, pregnancy loss, growth restriction, low birth weight, preterm birth, recurrence, and uncertainty. No publication bias was detected using Egger’s test. The overall AMSTAR 2 confidence rating for the included meta-analyses and systematic reviews was moderate. The majority (55.3%) of the evidence evaluated by GRADE was of low quality, while the remaining outcomes were categorized as having “very low”-quality evidence.ConclusionCurrent evidence links heart disease during pregnancy to adverse maternal outcomes, including death and cardiac, pulmonary, and cerebrovascular events, as well as increased mortality risk for offspring. Many meta-analyses in this field have limitations that raise concerns about their validity, highlighting the need for high-quality prospective studies.